Mercury pollution remediation in paddy fields with biochar amendment - Yanxin Hu; Chuan Wang; Junyao Yan; Ruolan Li; Rasheed Mohammed Abdul; Yan An; Jinjuan Li; Ping Li (Applied Geochemistry, 2026)

Porcine epidemic diarrhea virus influences the expression of tight junction proteins through the polarity protein PAR6 - Tingyu Hu; Ruolan Zhang; Qian Weng; Simin Wang; Yuheng Li; Zhihua Pei; Kai Wang; Guixue Hu (Virus Genes, 2026)

Optimization of Water-saving Performance under Green Finance: a Multi-perspective Game-theoretic Approach - Jie Zhang; Ruolan Sun; Yufei Hu (Water Resources Management, 2026)

Comprehensive single-cell profiling uncovers TsMHC-II expression predicting response to neoadjuvant immunotherapy in gastric cancer - Zhiyuan Xu; Zhichun Tang; Simeng Hu; Litao Yang; Jingli Xu; Pengfei Yu; Yian Du; Yanqiang Zhang; Jiahui Chen; Xiaoxiao Wu; Siwei Pan; ShengJie Zhang; et al. (Science Bulletin, 2026)

Exceptional methylmercury bioaccumulation in rice grain from karst region with high geological background - Langfei Wei; Shaochen Yang; Ruolan Li; Rasheed Mohammed Abdul; Yanxin Hu; Haiyu Yan; Baolin Wang; Haiyan Hu; Ping Li (Applied Geochemistry, 2026)

Functional differentiation of Sojae semen Praeparatum: A multi-omics analysis of the effects of Artemisia annua and Mori folium on composition, microorganisms, and functional characteristics - Yingying Cheng; Bing Wang; Qiaoling Ma; Min Sun; Xintong Wang; Ruolan Wang; Hongping Chen; Lin Chen; Youping Liu; Fu Wang; Chuan Zheng; Yuan Hu (Food Research International, 2025)

Edge-Based Dynamic Spatiotemporal Data Fusion on Smart Buoys for Intelligent Surveillance of Inland Waterways - Ruolan Zhang; Chenhui Zhao; Yu Liang; Jingfeng Hu; Mingyang Pan (Journal of Marine Science and Engineering, 2025)
Increasing vessel traffic in narrow, winding inland waterways has heightened the risk of accidents, driving the need for improved surveillance and management. This study addresses the challenge of real-time processing and synchronization of voluminous video and AIS data for effective waterway management. We developed a surveillance method utilizing smart buoys equipped with sensors and edge computing devices, enabling dynamic spatiotemporal data fusion. The integration of AIS data with advanced computer vision techniques for target detection allows for real-time traffic analysis and provides detailed navigational dynamics of vessels. The method employs an enhanced Long Short-Term Memory network for precise trajectory prediction of AIS data and a single-stage target detection model for video data analysis. Experimental results demonstrate significant improvements in ship detection accuracy and tracking precision, with an average position prediction error of approximately 1.5 m, which outperforms existing methods. Additionally, a novel regional division and a Kalman filter-based method for AIS and video data fusion were proposed, effectively resolving the issues of data sparsity and coordinate transformation robustness under complex waterway conditions. This approach substantially advances the precision and efficiency of waterway monitoring systems, providing a robust theoretical and practical framework for the intelligent supervision of inland waterways.

Injectable exosome-loaded quaternized chitosan/oxidized sodium alginate hydrogel with self-healing, bioadhesive, and antibacterial properties for treating combined radiation-wound injury - Guanqun Peng; Jia Hu; Jinnan Guo; Jiahui Dong; Yuanyuan Zhao; Tong Ye; Fengjun Xiao; Zhiyun Meng; Hui Gan; Ruolan Gu; Peng Han; Wenzhong Sun; et al. (Chemical Engineering Journal, 2024)

Rapid and highly sensitive colorimetric LAMP assay and integrated device for visual detection of monkeypox virus - Yadan Peng; Ruolan Hu; Shuang Xue; Yugan He; Lili Tian; Zehan Pang; Yile He; Yuqi Dong; Yinghan Shi; Shuqi Wang; Bixia Hong; Ke Liu; et al. (Analytica Chimica Acta, 2024)

Response of organic aerosol in Beijing to emission reductions during the XXIV Olympic Winter Games - Qipeng Qu; Shuxiao Wang; Bin Zhao; Ruolan Hu; Chengrui Liang; Haowen Zhang; Shengyue Li; Boyang Feng; Xuan Hou; Dejia Yin; Jinhong Du; Yangxi Chu; et al. (Science of The Total Environment, 2024)

Combined exposure of beta-cypermethrin and emamectin benzoate interferes with the HPO axis through oxidative stress, causing an imbalance of hormone homeostasis in female rats - Yuxin Li; Xianzhi He; Bin Sun; Nannan Hu; Jiamin Li; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Reproductive Toxicology, 2024)

Molecular tracers, mass spectral tracers and oxidation of organic aerosols emitted from cooking and fossil fuel burning sources - Chengrui Liang; Shuxiao Wang; Ruolan Hu; Guanghan Huang; Jinzi Xie; Bin Zhao; Yuyang Li; Wenfei Zhu; Song Guo; Jingkun Jiang; Jiming Hao (Science of The Total Environment, 2023)

Neuroprotective effect of green tea extractives against oxidative stress by enhancing the survival and proliferation of PC12 cells - Zhenlu Cai; Xiaoxuan Hu; Ruolan Tan; Yunran Feng; Meiqi Sun; Ning Ma; Xingxing Li; Li Huang; Jing An; Qian Ge; Haixia Lu (Molecular & Cellular Toxicology, 2019)

HIF-1α/Beclin1-Mediated Autophagy Is Involved in Neuroprotection Induced by Hypoxic Preconditioning - Na Lu; Xingxing Li; Ruolan Tan; Jing An; Zhenlu Cai; Xiaoxuan Hu; Feidi Wang; Haoruo Wang; Chengbiao Lu; Haixia Lu (Journal of Molecular Neuroscience, 2018)